CHARACTERISTICS OF BACTERIOCIN PRODUCING LACTOCOCCUS SPECIES ISOLATED FROM PROCESSED MEAT - Yurliasni - (Bionatura, 2009)
The bacteriocin producing Lactococcus species, isolated from processed meat (smoked beef) by serial dilution and poured plate inoculation were biochemically similar to Latococcus lactis subsp. lactis strain. The bacteriocin (s) produced by the three isolates have MW similar to nisin. They also have wider antibacterial range against Gram-positive pathogenic and spoilage bacteria similar to nisin. Plasmid profile showed UW1 and UW2 are similar but different from UW3 and all three isolates are different from the seven known nisin producing strain of L. lactis subsp. lactis. (DL, 150, 7690, Tis Sik, ATCC11454, 354/07, and 148). Furthermore, amino acid sequence analysis is needed to identify whether unknown bacteriocin is nisin or not. Keywords: Bacteriocin, isolates